Pengetahuan Masyarakat terhadap Pilihan Pengobatan Antara Medis Tradisional dan Medis Modern - Masrizal Masrizal; Zainal Arifin; Yevita Nurti (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
The aim of the research is to describe the public's knowledge of treatment options between traditional medicine and modern medicine. This study used an anthropological approach with qualitative methods through in-depth interviews, observation, literature study and documentation. The results of the study, namely education, economy and geographical location did not affect the people of Nagari Pauh IX in choosing treatment. The choice of treatment is determined by the healing factors of the disease which are influenced by the cultural knowledge of the community, the experience gained from family and society for generations. The conclusion of the research is that people's knowledge in influencing treatment choices includes knowledge about illness, types of illness, knowledge about the various conveniences obtained when seeking treatment, knowledge about traditional healers (traditional healers) and knowledge about the effectiveness of self-medicating, going to traditional healers, midwives, and doctors. Keywords: Knowledge, Modern Medicine, Traditional Medicine, Shaman.